Purchase of Own Stocks As A Means of Protection Against A Hostile Takeover of A Company By Applying The Principles of Corporate Social Responsibility: The Case of Croatia - Valentina VINSALEK STIPIC; Zlatko CESIC (Communications of International Proceedings, 2023)
This research work conducted a study that sought to prove the connection between the implementation of social and environmental sustainability with the profitability of enterprises and the creation of economic added value. Expressing social and environmental sustainability as numerical indicators is quite undefined, because companies in Croatia do not have a legal obligation to state them in their business reports and notes. It is just a measure to improve and raise business and market ratings. Therefore, for this research, data on social and environmental sustainability as measurable variables were obtained after a survey conducted among employees and company management on a sample of 126 Croatian companies. The obtained measurable variables for environmental and social sustainability were ultimately put into comparative analysis with the company's profitability indicators and the created economic added value. This research obtained data that there is a connection between environmental and social sustainability with the profitability of the company and the creation of economic added value, but it is extremely small, social sustainability 0.212 and environmental sustainability 0.243.
Keywords: Ecological sustainability; social responsibility; economic added value